2015
DOI: 10.1007/s13225-014-0319-0
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Stachybotrys (Memnoniella) and current species status

Abstract: Stachybotrys (asexual Hypocreales) has a worldwide distribution. This genus inhabits substrates rich in cellulose and is closely related to Memnoniella. Classification of species has previously been based on morphology, with conidial characters being considered as important. This study reevaluates Stachybotrys and Memnoniella, which is shown to include at least seven species-groups; while Memnoniella is a synonym of Stachybotrys. The sexual genera Ornatispora and Melanopsamma are also synonyms of Stachybotrys.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(81 citation statements)
references
References 133 publications
(149 reference statements)
6
72
0
Order By: Relevance
“…Peethambara was earlier classified as Hypocreales order incertae sedis (Castlebury et al 2004). In their revision, Crous et al (2014) showed Peethambara and related genera form a monophyletic lineage with Stachybotrys and introduced the novel family, Stachybotriaceae and this is supported in Wang et al (2015). (Sakayaroj et al 2011a).…”
Section: Neopestalotiopsismentioning
confidence: 94%
See 1 more Smart Citation
“…Peethambara was earlier classified as Hypocreales order incertae sedis (Castlebury et al 2004). In their revision, Crous et al (2014) showed Peethambara and related genera form a monophyletic lineage with Stachybotrys and introduced the novel family, Stachybotriaceae and this is supported in Wang et al (2015). (Sakayaroj et al 2011a).…”
Section: Neopestalotiopsismentioning
confidence: 94%
“…(type) based on gene sequence data (Castlebury et al 2004). Stachybotrys is the oldest name and is frequently used in literature and adopted by Wang et al (2015). Ornatispora is also a synonym.…”
Section: Savoryellaceaementioning
confidence: 99%
“…Studies found that ITS sequence data can act as a primary barcode for Myrothecium species because its sequence data can accurately identify the 73% of taxa studied across kingdom fungi and has a high sequence and PCR success rate [10]. ITS sequence data has been very much helpful for molecular systematics at the species level and even within the species [11]. In our case reports, we have identified the fungus was M. gramineum and M. verrucaria based on ITS sequence analysis.…”
Section: Discussionmentioning
confidence: 99%
“…These relatively well‐known metabolites are produced by several genera of fungi, including Tricothecium, Myrothecium, Baccharis and Stachybotrys . Because of their frequent occurrence in the environment and potential human impact, they garner continued interest . There is significant structural diversity in the macrocylic trichothecenes; often a plethora of these molecules are observed in fungal extracts leading to highly complex natural product mixtures.…”
Section: H and C Nmr Data For Roridin E (600 And 150 Mhz Cdcl3)mentioning
confidence: 99%